Agr-typing of methicillin-susceptible Staphylococcus aureus (MSSA) isolated from non-human primates - V. A. Kalashnikova (Ветеринария сегодня, 2020)
Staphylococcus aureus (S. aureus) is a microorganism that causes a great number of diseases in humans and animals, including sepsis, pneumonia, food toxicoinfections, wound abscess, etc. Numerous studies on genotyping S. aureus strains isolated from humans, food and mastitis in cattle and small ruminants have been carried out. The lack of information on the genotyping of methicillin-susceptible S. aureus detected in monkeys served as a stimulus to conduct a similar research, since staphylococcal infections in the primates are widespread. The present study is devoted to molecular genetic testing of S. aureus isolated from different biological samples taken from monkeys and is based on typing of agr polymorphic locus which acts as a regulator of pathogenic gene expression. As a result of PCR analysis of 301 S. aureus isolates it was established that most of S. aureus belonged to agr IV (55%), and agr I (34%) was the second most group. Data resulting from the study differ from the results of other researchers published in literary sources, who performed typing of salmonella isolated from people with agr I prevailing. In conducting the study, neither distinct correlation between microbial isolation source and agr complex groups, nor relationship between the diseases and S. aureus group specificity were detected. Prevalence ratio of each agr group is nearly similar in S. aureus isolated from rhesus macaques and crab-eating macaques. But in hamadryas baboons and green monkeys II and III groups of agr complex were not detected.